2013
DOI: 10.1002/2013jd020553
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of low clouds over the Arabian Sea

Abstract: [1] This paper studies climatically important low clouds (with cloud top below 680 hPa) over the Arabian Sea using the Kalpana-1 satellite data and International Satellite Cloud Climatology Project cloud data. Characteristics and possible mechanisms behind low-cloud formation in the summer monsoon season are presented. The dominant lower tropospheric circulation over the Arabian Sea during the summer season is the monsoon low-level jet (LLJ). Low clouds are predominantly found on the exit portion of the LLJ wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…The summer season extends from June to August and is greatly impacted by the Indian monsoon depression. The monsoon is associated with the low-level jet (LLJ) affecting the southern part of the peninsula (Sathiyamoorthy et al, 2013). The Tropic of Cancer, located under the descending limb of the Hadley cell, leads to the region being dominated by subtropical anticyclones, associated with air subsidence, stable conditions, and high pressure (Mandoos, 2006).…”
Section: Case Studymentioning
confidence: 99%
“…The summer season extends from June to August and is greatly impacted by the Indian monsoon depression. The monsoon is associated with the low-level jet (LLJ) affecting the southern part of the peninsula (Sathiyamoorthy et al, 2013). The Tropic of Cancer, located under the descending limb of the Hadley cell, leads to the region being dominated by subtropical anticyclones, associated with air subsidence, stable conditions, and high pressure (Mandoos, 2006).…”
Section: Case Studymentioning
confidence: 99%
“…The MLLJ is formed primarily from the cross‐equatorial flow induced by differential heating in the summer hemisphere (between the latitudes 20°N and 20°S), which creates pressure gradient forces of heat lows over the Indian subcontinent and Mascarene High (Krishnamurti and Bhalme, ; Murakami, ; Hart, ). MLLJ winds blow primarily at heights between 1,000 and 4,000 m, with a core of jet at around 1,500 m above mean sea level (Boos and Emanuel, ), transport moisture from the Southern to Northern Hemisphere (Cadet and Reverdin, ; Roxy et al ., ), and also control the formation and maintenance of monsoon inversion layers over the western central Arabian Sea (Sathiyamoorthy et al ., ; Dwivedi et al ., ). The MLLJ also plays a major role in modulating the amount of rainfall over the Indian subcontinent (Wu et al ., ), in the active‐break monsoon rainfall spells, and intra‐seasonal oscillations of the ISM (Sam and Vittal Murty, ; Joseph and Sijikumar, ).…”
Section: Introductionmentioning
confidence: 99%
“…() have shown that the atmospheric circulation and thermodynamical parameters (convective available potential energy and convective inhibition) are influenced by the sea surface temperature (SST). The variation of convection (Graham and Barnett, ; Woolnough et al, ; Masunaga and Kummerow, ; Krishnamurthy and Kirtman, ; Rajendran et al, ; Sabin et al, ; Rajendran et al, ) and cloudiness (Gadgil et al, ; Meenu et al, ; Rajendran et al, ; Sathiyamoorthy et al, ; Nair and Rajeev, ) with SST has been documented over the Indian Ocean. Gadgil et al .…”
Section: Introductionmentioning
confidence: 99%